Medium Optimization by Response Surface Methodology for Improved Cholesterol Oxidase Production by a Newly Isolated Streptomyces rochei NAM-19 Strain. - Elsayed, Elsayed Ahmed; Ahmed Abdelwahed, Nayera (BioMed Research International, 2020)
Cholesterol oxidase is an alcohol oxidoreductase flavoprotein with wide biotechnological applications. The current work describes the isolation of a potential cholesterol oxidase producing streptomycete from Egyptian soil. The isolated strain produced cholesterol oxidase in submerged culture using a medium containing glucose, yeast extract, malt extract, and CaCO3 with the addition of cholesterol as an inducer. The isolated strain was identified as Streptomyces rochei NAM-19 based on 16S rRNA sequencing and phylogeny. Optimization of cholesterol oxidase production has been carried out using response surface methodology. The Plackett-Burman design method was used to evaluate the significant components of the production medium followed by Box-Behnken experimental design to locate the true optimal concentrations, which are significantly affecting enzyme production. Results showed that the predicted enzyme response could be closely correlated with the experimentally obtained production. Furthermore, the applied optimization strategy increased volumetric enzyme production by 2.55 times (65.1 U/mL) the initial production obtained before medium optimization (25.5 U/mL).